Prolonged Clinical Stability in an Elderly Patient with Advanced Non-Small Cell Lung Carcinoma Under Palliative Homeopathic Management: A Comprehensive Serial Case Report - Rasel, Nur-E-Alam; Bhuyan, Mohammad Abul Hashem; Hossain, Mohammad Shahi Emran; Khalil, Md Ibrahim; Rume, Rumana Afroze (European Journal of Applied Sciences, 2026)
Background: Non-small cell lung carcinoma (NSCLC) is the most common type of lung cancer and remains a leading cause of cancer-related mortality worldwide, particularly in elderly patients who often present at advanced stages and are unsuitable for aggressive treatment. In such cases, palliative care plays a central role in improving symptom control and quality of life. Case Presentation: An 82-year-old male with CT-guided biopsy-proven adenocarcinoma of the left lower lobe was evaluated and deemed unfit for chemotherapy due to age and comorbid conditions. The patient underwent serial clinical, radiological, hematological, biochemical, and tumor marker assessments from February 2024 to January 2026. During this period, disease progression was observed radiologically and biochemically. Outcome: Despite progressive imaging findings and rising tumor markers, the patient demonstrated relatively stable general condition and maintained acceptable quality of life with supportive palliative care, including individualized homeopathic management. Conclusion: This case highlights the importance of continuous monitoring and palliative care in advanced NSCLC, where symptomatic stability and quality of life may be maintained even in the presence of disease progression. Further systematic studies are required to evaluate the role of individualized homeopathic approaches in integrative oncology settings.